2016
DOI: 10.1038/srep22572
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Related to the Chondrocyte ECM Regulates MMP13 Expression by Functioning as a MiR-136 ‘Sponge’ in Human Cartilage Degradation

Abstract: Circular RNAs (circRNAs) are involved in the development of various diseases, but there is little knowledge of circRNAs in osteoarthritis (OA). The aim of study was to identify circRNA expression in articular cartilage and to explore the function of chondrocyte extracellular matrix (ECM)-related circRNAs (circRNA-CER) in cartilage. To identify circRNAs that are specifically expressed in cartilage, we compared the expression of circRNAs in OA cartilage with that in normal cartilage. Bioinformatics was employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
239
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(243 citation statements)
references
References 40 publications
3
239
0
1
Order By: Relevance
“…Although the functions of circRNAs are yet largely unclear, accumulating evidence indicates their involvement in modulating the disease progression [41][42][43][44]. Thus, it is vital to understand the biological functions of circRNAs by investigating their expression patterns and interactions with other types of RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the functions of circRNAs are yet largely unclear, accumulating evidence indicates their involvement in modulating the disease progression [41][42][43][44]. Thus, it is vital to understand the biological functions of circRNAs by investigating their expression patterns and interactions with other types of RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have proved that circRNAs may regulate gene expression by manipulating miRNAs through its miRNA sponges function [36], and circRNAs also compete with mRNAs for miRNA binding in the cytoplasm and interfere in gene regulation [8]. MiRNAs control a large set of biological processes through direct interaction with their target mRNA, so circRNA sponge activity will also affect these pathways [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…45 Another study discovered a circRNA that functioned as a miR-136 sponge related to human cartilage degradation. 46 The mechanism of circRNAs Though the general mechanisms of circRNAs remain elusive, recent findings have indicated that circRNAs may interact with RNA or proteins and may serve as transcription or splicing regulators.…”
Section: Other Studiesmentioning
confidence: 99%